(untitled) (International journal of artificial intelligence, 2025)
The improvement of innovative methods in business management is a crucial factor in enhancing organizational performance, driving competitive advantage, and ensuring sustainable growth. This paper explores the role of innovation in business management, focusing on the implementation of cutting-edge strategies, technologies, and practices that can optimize operations, decision-making, and customer engagement. It examines the integration of digital transformation, data analytics, artificial intelligence, and agile methodologies into business management frameworks. The research highlights the benefits of adopting innovation-driven approaches, including increased efficiency, better resource allocation, and enhanced adaptability in a rapidly changing market environment.